Short- and Long-Term Effects of High-Intensity Interval Training vs. Moderate-Intensity Continuous Training on Left Ventricular Remodeling in Patients Early After ST-Segment Elevation Myocardial Infarction—The HIIT-EARLY Randomized Controlled Trial - Eser, Prisca; Trachsel, Lukas D.; Marcin, Thimo; Herzig, David; Freiburghaus, Irina; De Marchi, Stefano; Zimmermann, Andreas J.; Schmid, Jean-Paul; Wilhelm, Matthias (Frontiers in Cardiovascular Medicine, 2022)
Aim Due to insufficient evidence on the safety and effectiveness of high-intensity interval training (HIIT) in patients early after ST-segment elevation myocardial infarction (STEMI), we aimed to compare short- and long-term effects of randomized HIIT or moderate-intensity continuous training (MICT) on markers of left ventricular (LV) remodeling in STEMI patients receiving optimal guideline-directed medical therapy (GDMT). Materials and Methods Patients after STEMI (<4 weeks) enrolled in a 12-week cardiac rehabilitation (CR) program were recruited for this randomized controlled trial (NCT02627586). During a 3-week run-in period with three weekly MICT sessions, GDMT was up-titrated. Then, the patients were randomized to HIIT or isocaloric MICT for 9 weeks. Echocardiography and cardiopulmonary exercise tests were performed after run-in (3 weeks), end of CR (12 weeks), and at 1-year follow-up. The primary outcome was LV end-diastolic volume index (LVEDVi) at the end of CR. Secondary outcomes were LV global longitudinal strain (GLS) and cardiopulmonary fitness. Results Seventy-three male patients were included, with the time between STEMI and start of CR and randomization being 12.5 ± 6.3 and 45.8 ± 10.8 days, respectively. Mixed models revealed no significant group × time interaction for LVEDVi at the end of CR (p = 0.557). However, there was a significantly smaller improvement in GLS at 1-year follow-up in the HIIT compared to the MICT group (p = 0.031 for group × time interaction). Cardiorespiratory fitness improved significantly from a median value of 26.5 (1st quartile 24.4; 3rd quartile 1.1) ml/kg/min at randomization in the HIIT and 27.7 (23.9; 31.6) ml/kg/min in the MICT group to 29.6 (25.3; 32.2) and 29.9 (26.1; 34.9) ml/kg/min at the end of CR and to 29.0 (26.6; 33.3) and 30.6 (26.0; 33.8) ml/kg/min at 1 year follow-up in HIIT and MICT patients, respectively, with no significant group × time interactions (p = 0.138 and 0.317). Conclusion In optimally treated patients early after STEMI, HIIT was not different from isocaloric MICT with regard to short-term effects on LVEDVi and cardiorespiratory fitness. The worsening in GLS at 1 year in the HIIT group deserves further investigation, as early HIIT may offset the beneficial effects of GDMT on LV remodeling in the long term.